Pengaruh Organizational Justice terhadap Knowledge Sharing dengan Perceived Organizational Support dan Affective Organizational Commitment sebagai Variabel Intervening di Rumah Sakit Tria Dipa - Dinda Putri Husni; Andreas Wahyu Gunawan P (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of the study was to analyze the effect of Perceived Organizational Support and Affective Organizational Justice as intervening variables on the relationship between Knowledge Sharing and Organizational Justice at Tria Dipa Hospital. The methodology of this research is through surveys to collect data to test the research hypotheses. The type of research used is quantitative with the PLS-Structural Equation Modeling (SEM) approach using SMART PLS software. The sample used in this study were 132 medical and non-medical employees at Tria Dipa Hospital using purposive sampling method. This study has seven hypotheses and all of them are supported which states that there is an influence of Perceived Organizational Support and Affective Organizational Justice as intervention variables on the relationship between Knowledge Sharing and Organizational Justice. The managerial implication of the research is for the organization in this case the hospital management, the results of this study can be used as initial data based on descriptive statistics from the Organizational Justice variable, the lowest mean value is obtained regarding the imbalance received by the efforts made by employees, for the organization in this case. hospital management, the results of this study can be used as initial data based on descriptive statistics from the Knowledge Sharing variable, the lowest mean value is obtained regarding using the knowledge given by colleagues, for organizations in this case hospital management, the results of this study can be used as preliminary data based on descriptive statistics from the Percieved Organizational Support variable, obtained the lowest average value regarding obtaining a salary that is in accordance with responsibilities, for organizations in this case hospital management, the results of this study can be used as a or initial based on descriptive statistics of the Affective Organizational Commitment variable, obtained the lowest average value regarding the difficulty of leaving the company.